2008
DOI: 10.1897/07-277.1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a biomarker for metal bioavailability: The lettuce fatty acid composition

Abstract: Because Lactuca sativa L. is a plant widely used in ecotoxicological analyses, a study was developed to determine whether the fatty acid composition of lettuce leaves could be used as an additional biomarker of soil contamination by metals such as Pb, Cu, Zn, and Cd. Unlike seed germination or seedling growth, the fatty acid composition of lettuce leaves differed significantly between uncontaminated and field metal-contaminated soils. Hence, this lipid biomarker might provide an early indication of a plant's e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 20 publications
(19 reference statements)
3
10
0
Order By: Relevance
“…Also, it should be noted that in roots, excess Cd had a strong effect on total lipid concentration and fatty acid composition. In previous studies (Verdoni et al [2001]; Le Guédard et al [2008]) carried out with lettuce and tomato seedlings in a controlled environment, we showed that the percentage of tri-unsaturated fatty acids in leaves decreased while the percentage of C18:2, and to a lesser extent C18:1 and C18:0, increased, when plants were grown for 14 d on metal-contaminated soils. Hence, we proposed that the leaf fatty acid composition, and more precisely the C18:3/(C18:0 + C18:1 + C18:2) ratio could be used as an indicator of metal bioavailability and of their adverse effects on plants.…”
Section: Discussionsupporting
confidence: 53%
“…Also, it should be noted that in roots, excess Cd had a strong effect on total lipid concentration and fatty acid composition. In previous studies (Verdoni et al [2001]; Le Guédard et al [2008]) carried out with lettuce and tomato seedlings in a controlled environment, we showed that the percentage of tri-unsaturated fatty acids in leaves decreased while the percentage of C18:2, and to a lesser extent C18:1 and C18:0, increased, when plants were grown for 14 d on metal-contaminated soils. Hence, we proposed that the leaf fatty acid composition, and more precisely the C18:3/(C18:0 + C18:1 + C18:2) ratio could be used as an indicator of metal bioavailability and of their adverse effects on plants.…”
Section: Discussionsupporting
confidence: 53%
“…Alpha-linolenic acid may reduce arachidonic acid (ARA; 20:4n-6) levels by competing with LA for the same metabolic enzymes (e.g., responsible for the elongation of n-6 FA), reduces the levels of serum triglycerides and displays anti-inflammatory properties, which may help in the prevention of cardiovascular diseases and has a positive effect on the recovery of central nervous system injuries [63]. A predominance of ALA and LA was also observed in other vegetables, including lettuce [64]. In general, the FA profiles of the reported Sarcocornia species are similar to those described for Salicornia [12,13,65,66].…”
Section: Fatty Acids (Fa)mentioning
confidence: 99%
“…Another leaflet of this leaf (number 3 from the collar) is used for analyzing the fatty acids [phospho-lipidic fatty acids (PLFA) trans-methylated to yield analyzable fatty acid methyl esters (FAME)] according to the norm Afnor X31-233 on the determination of the effects of microcystins on the foliar fatty acid content of Lactuta sativa (AFNOR 2012; Le Guedard et al (2008) and suitable for tomatoes (Verdoni et al 2001). The fatty acid composition was used as biomarker of contaminated soil with metallic or organic pollutants.…”
Section: Physiological Parameters Of Plantsmentioning
confidence: 99%